Stylistic Deviation in Devkota's “The Lunatic” - Tumbahang, Mohan Kumar (JODEM: Journal of Language and Literature, 2022)
This article explores the linguistic deviations especially on two levels: semantic and syntactic levels. Out of few Devkota's intricate poetic compositions, "The Lunatic" is considered to be the daunting poems to the average readers, students, and even teachers. Not only its English version "The Lunatic", but its Nepali version "Paagala" also can pose an equal degree of toughness to the Nepali readers. The article seeks the answers to the questions as: what sorts of semantic and syntactic deviations are there in the poem "The Lunatic"? How do these deviations occur in the poem, and why have these deviations been used there? The article focuses on the main words which have distorted the meaning system in terms of the ordinary norms of grammar. Similarly, it also points out the syntactic patterns which have overtly flouted the grammatical norms. Furthermore, it aims to discuss the motives behind the deliberate break of the rules. This article is mainly based on stylistic approach to literary theory with qualitative design. For the theoretical insights, certain related books by Shklovsky (1987), Leech (1988), and Lazar (1993) were duly consulted. After the analysis of the obtained data, it was found out that there were a considerable number of deviations on the levels of word-meaning and the word-order in the pattern of poetic expression. The sole motive of deviant text is the stylistic purpose and enhancement of the expressive range.